Increasing Students’ Vocabulary Through Online Crossword Games - Imbenay, Joceline Oktorinna Inggerus; Katemba, Caroline V. (8ISC Proceedings: Arts and Education, 2022)
Vocabulary is one of many sub-skills that is very important in learning a language to make a sentence, communicate, and especially in improving the four skills: listening, speaking, reading, and writing. The lack of vocabulary is one aspect that really can make students lazy in learning a language, especially in the English language. This research aims to look at the use of the game Cross Word in online learning to teach vocabulary. This study used semi-experimental research to gather the data and teach vocabulary practices using the game Cross Word application. The number of participants was sixteen and were around 12 years old from SD Advent Bendungan Hilir. The researcher conducted the research at SD Advent Bendungan Hilir was taken as the experimental group. The experimental group consisted of 16 students. A pre-test was conducted at the beginning. The researcher began using the game crossword application and used the game Cross Word application, and then the post-test was given after 32 hours. Based on the research results, although it is used as a method in the teaching and learning process of English, the game Cross Word application has significant advantages in developing student vocabulary, and it is also suggested that the game Cross Word application be used as a tool in English teaching and learning process. Keywords : vocabulary, Cross Word, experimental, elementary